2020
DOI: 10.1186/s40850-020-00055-5
|View full text |Cite
|
Sign up to set email alerts
|

Response of a rice insect pest, Scirpophaga incertulas (Lepidoptera: Pyralidae) in warmer world

Abstract: Background Increases in global mean temperature, changes in rainfall patterns, and extreme climatic events are expected results of climate change. The individual effects of elevated temperature and precipitation on insect pests due to the impact of climate change have been widely modeled individually but their combined effects are poorly understood. Results Ten years of monthly abundance of an important economic rice insect pest, the rice yellow stem borer (YSB), Scirpophaga incertulas Walker (Lepidoptera: Py… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…To illustrate, the populations of Scirpophaga incertulas (Walker) exhibited an upsurge during the periods of elevated temperatures coupled with diminished rainfall. Conversely, instances of elevated temperatures accompanied by increased rainfall resulted in a decline in S. incertulas populations (Ali et al., 2020). In parallel, the population of Cnaphalocrocis medinalis (Guenée) experienced an upswing as temperatures and precipitation levels rose (Paschapur et al., 2022).…”
Section: Discussionmentioning
confidence: 99%
“…To illustrate, the populations of Scirpophaga incertulas (Walker) exhibited an upsurge during the periods of elevated temperatures coupled with diminished rainfall. Conversely, instances of elevated temperatures accompanied by increased rainfall resulted in a decline in S. incertulas populations (Ali et al., 2020). In parallel, the population of Cnaphalocrocis medinalis (Guenée) experienced an upswing as temperatures and precipitation levels rose (Paschapur et al., 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Climate change is expected to affect the behavior as well as distribution and abundance of YSB in southern Asia by increasing winter survival rates and the number of generations per year, as well as inducing an earlier appearance in the crops after winter (Patel et al, 2017) [24] . However, Ali et al, 2020 [2] found that the development rate of yellow stem borer was positively impacted by both rising temperatures and rainfall when taken separately. Nevertheless, there was a deleterious outcome when rainfall and high temperatures were coupled.…”
Section: Impact Of Climate Change On Rice Pestsmentioning
confidence: 99%
“…Moreover, the concomitant high temperature is expected to lead to reduced yield by unfavorable effects on pollen development and sink starch metabolism [5]. High temperature also accelerates the growth rate of crop damaging insect pests such as yellow stem borer [6]. Increased emergence of such pest challenges, quickly becoming critical, can happen in much shorter timelines than the variety breeding cycles.…”
Section: Introductionmentioning
confidence: 99%